Alexis gets frosted - Simon, Coco (Simon, Coco. Cupcake diaries ;, 2013)
When Sydney moves away and is replaced by newcomer Olivia, Alexis becomes the focus of hurtful teasing by the Best Friends Club and begins to wonder if an offhand remark she made when first meeting Olivia may have been taken the wrong way.